TASA formulation for nonlinear radiative flow of Walter-B nanoliquid invoking microorganism and entropy generation - T. Hayat; Aqsa Razzaq; Sohail A. Khan; Aneeta Razaq (Results in Engineering)
Recent scientists and engineers have keen interest for nanomaterial flow across the globe. It is because of the fact that nanomaterials possess innovative characteristics that have gained considerable attention for their involvement in medicine, automobiles, metal spinning, heat transfer and storage devices, power generation, renewable energy and many others. Heat transfer rate has key role regarding finishing and quality of end product. With such consideration the present communication analyzes magnetohydrodynamic bioconvective flow of Walter-B nanoliquid. Flow is generated by stretching surface. Gyrotactic microorganisms in presence of first order reaction is discussed. Energy expression comprises Brownian movement, magnetohydrodynamics, thermophoresis, thermal radiation and dissipation characteristics. Innovative features (random movement and thermophoresis) of Buongiorno's model are deliberated. Entropy minimization rate is under consideration. Soret effect in first order reactive flow is considered. Bejan number is calculated. Dimensionless ordinary expressions are developed through suitable transformations. Optimal homotopy analysis method (OHAM) is invoked for convergence purposes. Total and individual residual errors have been computed through OHAM which guarantees the solutions convergence. Graphical analysis for entropy rate, microorganism field, liquid motion, temperature, Bejan number and concentration is arranged. In addition, the analysis for skin friction, motile density number and Nusselt and Sherwood numbers is organized. Here velocity and Bejan number decreased against larger magnetic field whereas opposite scenerio witnessed regarding thermal field and entropy rate. Decrease in liquid motion occurs through viscoelastic variable while an increasing effect seen for thermal transport rate. Higher Prandtl number lead to intensify the thermal transport rate. Nusselt number and entropy rate for radiation have similar response qualitatively when compared with concentration through higher Soret number.